2012
DOI: 10.1371/journal.pgen.1002451
|View full text |Cite
|
Sign up to set email alerts
|

A High Density SNP Array for the Domestic Horse and Extant Perissodactyla: Utility for Association Mapping, Genetic Diversity, and Phylogeny Studies

Abstract: An equine SNP genotyping array was developed and evaluated on a panel of samples representing 14 domestic horse breeds and 18 evolutionarily related species. More than 54,000 polymorphic SNPs provided an average inter-SNP spacing of ∼43 kb. The mean minor allele frequency across domestic horse breeds was 0.23, and the number of polymorphic SNPs within breeds ranged from 43,287 to 52,085. Genome-wide linkage disequilibrium (LD) in most breeds declined rapidly over the first 50–100 kb and reached background leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
191
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(207 citation statements)
references
References 40 publications
13
191
1
2
Order By: Relevance
“…Third, we capitalized on the recent publication of known genotypes at 54,602 SNP loci for ca. 400 horses from 32 modern domesticated breeds (8). We examined whether domesticated alleles at each locus coalesce more recently than ancient alleles, as would be expected if domestication results in a selective sweep.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, we capitalized on the recent publication of known genotypes at 54,602 SNP loci for ca. 400 horses from 32 modern domesticated breeds (8). We examined whether domesticated alleles at each locus coalesce more recently than ancient alleles, as would be expected if domestication results in a selective sweep.…”
Section: Methodsmentioning
confidence: 99%
“…horses (7,8). Instead, it likely represents a sister population that separated from the ancestral population of domesticated horses some 38-72 kya (9).…”
Section: Significancementioning
confidence: 99%
“…Previous studies have demonstrated that robust phylogenetic signal can be obtained by querying domestic animal SNP arrays with DNA from related species of the same genus, family, or order, despite having diverged tens of millions of years from the array reference genome (Decker et al 2009;McCue et al 2012). Here, we generated genome-wide SNP data from 38 cat species and analyzed these separately and together with Y-linked variation and whole mitogenomes, allowing us to disentangle different maternal, paternal, and biparental histories within a diverse family of mammals.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…The resultant scatter plots are known as Manhattan plots because they resemble the skyline of a major city with some points that tower over the majority of others. Determining the genome sequence of the domestic horse led to the development of 2 equine SNP arrays that could be used for GWAS by researchers 32, 39…”
Section: Genome‐wide Association Studiesmentioning
confidence: 99%
“…For example, the EquineSNP70 BeadChip Array1 contains approximately 74,000 SNPs positioned across the equine genome that can be simultaneously tested to identify their associations with a phenotype of interest 39, 40. Recently, a higher density SNP array with approximately 770,000 SNPs across the equine genome has been developed but has not been characterized in peer‐reviewed literature to date.…”
Section: Genome‐wide Association Studiesmentioning
confidence: 99%